THE INFLUENCE OF LIQUIDITY, PROFITABILITY AND SOLVENCY ON AUDIT DELAY IN ENERGY SECTOR COMPANIES LISTED ON THE IDX IN 2020-2022 - Annisa Nafatul Jannah; Hasim As’ari (Jurnal Ekonomi, 2023)
The purpose of this study is to ascertain how liquidity, profitability, and solvency affect audit delay. This study employs quantitative techniques. Employed in this study is the population of energy sector companies listed between 2020 and 2022 on the Indonesian Stock Exchange. This study employed the purposive sampling method as its sampling technique. 180 organisations made up the entire research sample from 2020 to 2022. This study employs several different analytic techniques. The study's findings indicate that while the significant value for profitability is 0.417, the variables for liquidity and solvency have no bearing on audit delay because their significant values are greater than 0.05.